Making decisions well and badly: How stakeholders' discussions influence individual executives' decision confidence and competence - De Villiers, R.; Hankin, R.; Woodside, Arch (2016)
This chapter presents a new model for developing and assessing the decision competencies of executive decision-makers. Prior models consider individual and group decision-making but neglect to consider the impact of groupinteractive decision-making on real-world problem-solving and sense-making activities. In the present study experimental protocols represent an approximation of a realistic business decision-making process, where decision-makers consult with groups of stakeholders and then make decisions on their own. The model juxtaposes decision competence with the level of decision confidence with which decisions are made. The study furnishes an objective test for this phenomenon, resulting in quantitative empirical evidence of either follow-the-herd (FTH) behavior, or group-forged individual decisions (GFID), or follow-my-own-mind (FMOM) individual decision behavior. The study investigates the impact of group-interactive decision processes on hubristic behavior decision-makers who make poor/wrong decisions, but remain confident in their choices, judgments, and decisions. The resulting management decision competency model provides an inter-disciplinary matrix, of benefit to human resource development specialists, and provides scholars in organizational behavior and leadership development with guidance for current and future research into group dynamics and decision competencies.